(untitled) (Research, Society and Development, 2020)
The article approaches a discussion about the Practice as Curriculum Component (PCC) in the initial formation of chemistry teachers with a look at both its organization and evidence of conception of practice that is being proposed. Attention is also paid to legislation guiding initial teacher education and defining the workload to be allocated to the CCP. The methodology is qualitative with the use of discursive textual analysis to construct the results. The data were obtained from the reading of Pedagogical Projects of Chemistry Degree Courses in Southern Brazil, selected via the e_MEC website. The analysis of the Pedagogical Projects inferred in two categories an a priori entitled “The Implementation / Effectiveness of the CCP in the pedagogical proposals of the courses”, from which two subcategories emerged: “Organization of the CCP: Curriculum Articulations” and “Organization of the CCP: Modes of Effect and execution of the CCP ” and an emerging category entitled“ The CCP as a way of qualifying the Teacher’s Professional Identity ”. In general, it was possible to infer that the insertion of the 400h of CCP may qualify the theory and practice relationship, but its real potentiality is related to the commitment and collective of the teacher trainers, thus, we point out the need for constant monitoring with the spaces. initial training as a means of qualifying such training.